Comparison of Intra-Operative and Post-Operative Complications between Non-Descent Vaginal Hysterectomy and Total Abdominal Hysterectomy - Afroz, Sayma; Ara, Gulshan (Journal of Enam Medical College, 2018)
Background: Hysterectomy is one of the most common surgical procedures performed by the gynaecologists and can be done through abdominal and vaginal routes. Vaginal hysterectomy technique has been introduced and performed centuries back, but is less popular due to lack of experience and misconception that the abdominal route is easier and safer. Worldwide gynaecologists continue to use abdominal route for hysterectomy that could be performed vaginally which is less invasive and has minimal complications. Objective: To compare the complications during intra-operative and post-operative period between vaginal hysterectomy and abdominal hysterectomy in non-descent uterus. Materials and Methods: This prospective randomised study was performed in Enam Medical College & Hospital, Savar, Dhaka during a period of one year. Sixty consecutive patients requiring hysterectomy for benign diseases were included in this study. Group A (n=30) underwent vaginal hysterectomy (non-descent vaginal hysterectomy) and were compared with Group B (n=30) who underwent abdominal hysterectomy. The primary outcome measures were operative time, intra-operative blood loss, post-operative complications like wound infection, febrile morbidity, post-operative systemic infection and hospital stay. Secondary outcome measures were conversion of vaginal to abdominal route and re-laparotomy. Data were collected in structured questionnaire and analysed by computer using R programming version 3.4.3. Results: Baseline characteristics were similar in two groups. There were no intra-operative complications in either group. Intra-operative blood loss was significantly more in Group B than in Group A. The overall complication rate was significantly higher with abdominal hysterectomy with a rate of 56.67% against 30% for vaginal hysterectomy. Wound infection (23.33%) was significantly higher in Group B as compared to Group A (0%). Post-operative hospital stay was significantly higher in Group B (7.03 days) than in Group A (4.57 days). Conclusion: Considering intra-operative blood loss, post-operative complications and hospital stay, vaginal route was found safer than abdominal route in this study. J Enam Med Col 2018; 8(3): 128-134